Pengaruh Teknik Role Playing Terhadap Penurunan Bullying Verbal Dikelas VIIIB MTs Al-Ma’arif Wuluhan - Arifin Nur Budiono; Muhammad Nur Salim (FKIP Universitas Islam Jember, 2018)
Bullying is defined as repeated aggression carried out by one or more people who aim to harm or disturb others physically, verbally or psychologically. Verbal bullying is a desire to harm or disturb other people in a non-physical manner which includes: 1) calling names of ridicule, 2) extortion, 3) threatening, 4) swear words, 5) taunting friends. This research was conducted in class VIIIb of MTs. Al-Ma'arif Wuluhan. This research used quantitative approach of a pre-experimental with one group pretest design. The population in this study was all eighth grade students of MTs. Al - Ma'arif Wuluhan and the sample was taken using purposive sampling. The data collection techniques used in this study were observations, interviews, and questionnaires which were then analyzed using the Wilcoxom test. The results of research on verbal bullying behavior has decreased from the role playing technique to verbal bullying behavior of class VIIIb MTs AL-MA'ARIF students. It can be seen from Z count (0, 186)> Z table (0.05) which means H0 is rejected and H1 is accepted. Keyword: role playing, verbal bullying